Employing MPI_T in MPI Advisor to optimize application performance. (November 2018) - Gallardo, Esthela; Vienne, Jérôme; Fialho, Leonardo; Teller, Patricia; Browne, James
MPI_T, the MPI Tool Information Interface, was introduced in the MPI 3.0 standard with the aim of enabling the development of more effective tools to support the Message Passing Interface (MPI), a standardized and portable message-passing system that is widely used in parallel programs. Most MPI optimization tools do not yet employ MPI_T and only describe the interactions between an application and an MPI library, thus requiring that users have expert knowledge to translate this information into optimizations. In contrast, MPI Advisor, a recently developed, easy-to-use methodology and tool for MPI performance optimization, pioneered the use of information provided by MPI_T to characterize the communication behaviors of an application and identify an MPI configuration that may enhance application performance. In addition to enabling the recommendation of performance optimizations, MPI_T has the potential to enable automatic runtime application of these optimizations. Optimization of MPI configurations is important because: (1) the vast majority of parallel applications executed on high-performance computing clusters use MPI for communication among processes, (2) most users execute their programs using the cluster's default MPI configuration, and (3) while default configurations may give adequate performance, it is well known that optimizing the MPI runtime environment can significantly improve application performance, in particular, when the way in which the application is executed and/or the application's input changes. This paper provides an overview of MPI_T, describes how it can be used to develop more effective MPI optimization tools, and demonstrates its use within an extended version of MPI Advisor. In doing the latter, it presents several MPI configuration choices that can significantly impact performance, shows how use of information collected at runtime with MPI_T and PMPI can be used to enhance performance, and presents MPI Advisor case studies of these configuration optimizations with performance gains of up to 40%.